2003
DOI: 10.1095/biolreprod.102.007492
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Regulates Growth, But Not Atresia, of Mouse Preantral and Antral Follicles1

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that binds various environmental contaminants. Despite our knowledge regarding the role of the AhR in mediating toxicity, little is known about the physiological role of the AhR. Previous studies indicate that the AhR may regulate folliculogenesis, because AhR-deficient (AhRKO) mice have fewer preantral and antral follicles than wild-type (WT) mice during postnatal life. Thus, the first objective of the present study was to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…Abbott et al described that AhR Ϫ/Ϫ females exhibited difficulties in maintaining conceptuses during pregnancy (1), while Benedict et al reported that AhR deficiency affected follicular maturation and ovulation under normal growth conditions (3,4). Our studies indicated that follicles present in the ovaries of AhR Ϫ/Ϫ mice developed to an antral/preovulatory stage, while the corpus luteum was barely detectable.…”
Section: Reproductive Defects Seen With Ahrmentioning
confidence: 46%
“…Abbott et al described that AhR Ϫ/Ϫ females exhibited difficulties in maintaining conceptuses during pregnancy (1), while Benedict et al reported that AhR deficiency affected follicular maturation and ovulation under normal growth conditions (3,4). Our studies indicated that follicles present in the ovaries of AhR Ϫ/Ϫ mice developed to an antral/preovulatory stage, while the corpus luteum was barely detectable.…”
Section: Reproductive Defects Seen With Ahrmentioning
confidence: 46%
“…Various xenobiotics, such as Congo red, VCH and its active metabolite, cyclophosphamide, and several aromatic hydrocarbons, benzo[a]pyrene, 3-methyl-cholanthrene and 7,12-dimethyl-benz [a]antrathene, are known to target primordial, primary and preantral follicles (for review, see Hoyer and Sipes, 1996;Gray, 1997). In addition, aryl hydrocarbon receptor, the receptor for 2,3,7,8-tetrachlorodibenzo-p-dioxin and coplanar polychlorinated biphenyls, contributes to the slowing of the initial and early recruitment of follicles (Benedict et al, 2000). In evaluating the ability of various xenobiotics to affect the number of primordial follicles, the concentration of circulating inhibin during the neonatal and infantile periods may be a useful indicator in the rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…During normal estrous, hormonal signals induce maturation of the granulosa cell layer surrounding the oocyte and trigger release of the follicle into the fallopian tube (Gilbert, 2000). Although the number and morphology of immature, preovulatory follicles is unchanged between wildtype and Ahr knockout females, several reports have noted a marked reduction in the number of mature follicles (Benedict et al, 2000(Benedict et al, , 2003Baba et al, 2005). Evidence indicates that these defects are not due to upstream changes in the endocrine regulation of ovulatory-stimulating hormones (Baba et al, 2005;Trewin et al, 2007).…”
mentioning
confidence: 99%
“…In addition to being refractory to most, if not all, aspects of TCDD toxicity, "Ahr-knockouts" exhibit multiple physiological abnormalities that are independent of xenobiotic exposure (Fernandez-Salguero et al, 1995;Schmidt et al, 1996;Mimura et al, 1997). Studies of the mutant mouse models have reproducibly demonstrated that the AHR has an intrinsic role in diverse aspects of mammalian biology that extend beyond (or are entirely independent from) xenobiotic metabolism (Andreola et al, 1997;Fernandez-Salguero et al, 1997;Zaher et al, 1998;Abbott et al, 1999;Benedict et al, 2000Benedict et al, , 2003Lahvis et al, 2000;Thackaberry et al, 2002;Lund et al, 2003Lund et al, , 2005Vasquez et al, 2003;Corchero et al, 2004;Guo et al, 2004;Baba et al, 2005;Lahvis et al, 2005). Moreover, these studies of null models have led to speculation that aspects of TCDD toxicity may be the result of sus-tained interference in these endogenous, physiological pathways mediated by the AHR.…”
mentioning
confidence: 99%